Hourly probabilistic snow forecasts over complex terrain: A hybrid ensemble postprocessing approach - Reto Stauffer; Georg J. Mayr; JakobW. Messner; Achim Zeileis (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
Accurate and high-resolution snowfall and fresh snow forecasts are important for a range of economic sectors as well as for the safety of people and infrastructure, especially in mountainous regions. In this article a new hybrid statistical postprocessing method is proposed, which combines standardized anomaly model output statistics (SAMOS) with ensemble copula coupling (ECC) and a novel re-weighting scheme to produce spatially and temporally high-resolution probabilistic snow forecasts. Ensemble forecasts and hindcasts of the European Centre for Medium-Range Weather Forecasts (ECMWF) serve as input for the statistical postprocessing method, while measurements from two different networks provide the required observations. This new approach is applied to a region with very complex topography in the Eastern European Alps. The results demonstrate that the new hybrid method not only allows to provide reliable high-resolution forecasts, it also allows to combine different data sources with different temporal resolutions to create hourly probabilistic and physically consistent predictions.
Keywords: 330; meteorology; ensemble postprocessing; standardized anomalies; copula coupling; high-resolution; fresh snow; snowfall